Synthesis of stainless steel/CNTs nanocomposite powders - Duanghathai Kaewsai (2018)
Stainless steel/carbon nanotubes (CNTs) nanocomposite powders were synthesized by chemical vapor deposition (CVD) method with ethanol as a carbon source. The effects of synthesis temperature and time on microstructure and chemical composition of the powders were investigated. The as-received stainless steel powders were synthesized at temperature in between 550-800°C for 30-180 min at a pressure of 10 Torr. The optimum synthesis condition was found to be 800°C for 120 min. Average diameter of CNTs grown on stainless steel particles slightly increased with increasing growth temperature. The synthesis time, however, was found to have no effect on the size of CNTs. © (2010) Trans Tech Publications.